Structure modification of 0–3 piezoelectric ceramic/polymer composites through dielectrophoresis - Wilson, Stephen A.; Maistros, George M.; Whatmore, Roger W. (Institute of Physics (IOP), 2005)
Anisotropic material properties can be induced in ceramic/polymer composites by applying an alternating electric field of moderate strength during processing. Under suitable conditions, particles of a ceramic filler material that are randomly dispersed in a liquid polymer or pre-polymer can be polarized and they then exhibit a collective response to localized gradients in the electric field. Typically, the particles experience a mutually attractive force which causes them to form 'pearl-chains' or columnar structures spanning the gap between electrodes. If the fluid is solidified, for example by curing the polymer resin, then the newly formed structures can be fixed in place to produce a composite with directional electrical and mechanical properties. Direct visual observations were made for low volume fraction dispersions of pure lead titanate in an epoxy pre-polymer under the influence of an electric field. The observed interaction was correlated with low-field dielectric measurements and existing theory to identify optimum assembly conditions. The dielectric properties of the fluid are predominant and the formation of chain-like structures is found to be both field strength and field frequency dependent. The dielectric permittivities of a range of structurally modified composites were measured and compared with existing theoretical models of di-phasic materials.